Penyelenggaraan Operasional Anggota Patroli Jalan Raya dalam Melaksanakan Tugas Pengawalan VVIP Maupun VIP di Wilayah Hukum Polda Bali Menurut Undang-undang Nomor 22 Tahun 2009 - Berliana Indah Sari; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2021)
In the jurisdiction of the Bali Police, there are also VIP and VVIP escorts which are special escorts from the Police for working visits of government officials visiting the Unitary State of the Republic of Indonesia. In carrying out these mentoring activities, it must be in accordance with the established Standard Operating Procedure (SOP). This study aimed to examine the legal arrangements regarding the security of escorts carried out by Polri members on the way to their destination and reveal the sanctions received by Polri members in carrying out escorts that are not in accordance with Standard Operating Procedures. This study used a normative legal approach to problems and legislation. Sources of data used were primary data and secondary data obtained through reading and taking notes. Furthermore, the data were analyzed descriptively qualitatively. The results of the study indicated that the right to escort is also regulated in Law No. 22 of 2009 Article 134 concerning Road Traffic and Transportation. Sanctions received by Polri members who do not enforce discipline in escort are contained in Government Regulation of the Republic of Indonesia Number 2 of 2003 concerning Discipline of Polri Members or sanctions for violating the implementation of Polri's professional code of ethics as regulated in National Police Chief Regulation Number 14 of 2011 concerning Polri's Professional Code of Ethics.